Fabrication of micro-array structures on material surface by a piezo-driven device. (September 2022) - Li, Xuan; Xu, Zhi; Sun, Wuxiang; Huang, Hu
Abstract: Fabricating micro-array structures on material surface is a useful method to enhance the functional application of materials. In this study, for fabricating micro-array structures on material surface in a convenient operation and low cost way, a three-axes piezo-driven device with features of compact structure and easy control strategy was developed. The device mainly consisted of a two-degrees of freedom piezo-driven positioning stage for controlling the sample movement along x and y axes, an indentation unit for generating the indent, and a frame. Micro-array indent structures were attempted to be fabricated on Ti6Al4V and Al1015 material surfaces, and experimental results showed that regular micro-array indent structures were successfully produced. Furthermore, by tuning the time-sequential control waveform of three piezoelectric stacks (PESs), the size, depth, and interval between two adjacent indents can be easily changed, forming various micro-array indent structures. Highlights: A three-axes piezo-driven device was developed for fabricating micro-array structures on material surface. The fabrication principle and control strategy were discussed. Regular micro-array indent structures were fabricated on Ti6Al4V and Al1015 material surfaces. The size, depth, and interval between two adjacent indents could be easily tuned.